Determinan keputusan nasabah menggunakan produk perbankan (studi kasus nasabah Bank Syariah Indonesia Kantor Cabang Pembantu Muara Bulian) - Rahayu, Vika Indah; Damanik, Eva Setiarini; Efrina, Liona; Primadiva, Parassela Pangestu (Jurnal Paradigma Ekonomika, 2023)
This study aims to determine service, bank characteristics, knowledge, location on customer decisions in using Bank Syariah Indonesia (Case Study of Muara Bulian Central Branch Office). This study used a sampling technique with a sample of 100 customers of Bank Syariah Indonesia Muara Bulian Sub-Branch Office. The method of this research is to use a qualitative research method with the help of the SPSS application as a means of calculating the data that has been obtained. This study uses 4 variables, namely service, bank characteristics, knowledge, location. The results of this study show that partially the characteristics of the Bank are in the very good category, namely the index value is 4.87, Service is in the good category at 4.11, Knowledge is in the fairly good category at 3.4, and Location is in the good category at 3.9.